Urban Space Remembered: University Students' Image of Bursa - Eklemezler, Sercan (İdeal Kent Yayınları, 2022)
This study examines how the city is perceived, learned and remembered by university students, some of whom have been in the city for education, some have been residents for a long time or since born. Characteristics defining the city; spatial elements with their focal points, landmarks, regions, borders, roads, also memory personalities of Bursa in the minds of the students, were investigated. The study also investigates the aspects of Bursa that are stressed in the literature, to consider the continuity of the Bursa image in the urban memory and compare it with students’ perspectives. Semi-structured interviews with 143 students and mind-maps drawing with 20 students were conducted to identify urban images which have the potential to be an identity element. Descriptive and comparative thematic analyses were made, frequency tables, code-subcode-segments, co-occurrence of codes models were extracted, and code-matrix-browser visuals were given. The results suggest that the perception of "Green Bursa" is anchored to the city, Uludağ, Ulu Cami, Tophane are the most dominant elements, and the city is mostly imaged with landmarks. To conclude, revealing the city images of students in a comparative way will contribute to understanding change in the urban identity of Bursa.

Bu çalışmada bir kısmı öğrenimleri nedeniyle kentte bulunan, diğer bir kısmıysa daha uzun süredir ya da doğduğundan bu yana kent sakini olan üniversite öğrencileri tarafından kentin nasıl algılandığı, öğrenildiği ve hatırlandığı ele alınmıştır. Kenti tanımlayan özellikler; odakları, nirengileri, bölgeleri, sınırları, yolları ile birlikte mekânsal öğeler; öğrencilerin zihninde Bursa ile özdeşleşmiş hafıza kişilikler araştırılmıştır. Bursa imgesinin kentsel hafızadaki sürekliliğine bakabilmek ve öğrencilerinkiyle karşılaştırabilmek adına literatürde Bursa’nın hangi yönleriyle öne çıkmış olduğuna da bakılmıştır. Kimlik öğesi olma potansiyeli yüksek kentsel imgelerin tespiti amacına yönelik olarak 143 öğrenci ile yarı yapılandırılmış görüşmeler ve 20 öğrenciyle zihin haritası çizimleri gerçekleştirilmiştir. Bunların betimsel ve karşılaştırmalı tematik analizleri yapılmış; sıklık tabloları, kod-alt kod-bölümler ve kod birlikte oluşma modelleri çıkarılmış, kod matris tarayıcısı görselleri verilmiştir. Elde edilen bulgularda, “Yeşil Bursa” algısının kente demirlendiği, Uludağ, Ulu Cami ve Tophane’nin kent imgesindeki en baskın öğeler oldukları ve kentin daha çok nirengilerle imgelendiği sonucuna varılmıştır. Kentteki toplumsal gruplardan biri olan üniversite öğrencilerinin kent imgelerini, karşılaştırmalı bir şekilde ortaya koymanın Bursa kent kimliğinin değişimini anlamaya katkı sunması beklenmektedir.
Hatırlanan Kentsel Mekân: Üniversite Öğrencilerinin Bursa İmgesi
-